Organizational Change in Human Service Organizations: A Review and Content Analysis. Issue 1 (1st January 2022) - Graham, John R.; Woodmass, Kyler; Bailey, Quinn; Li, Eric P. H.; Lomness, Arielle
ABSTRACT: This literature review examines organizational change scholarship within human service organizations ("health, " "human, " and "social" services) between 1968 and 2020. MEDLINE, CINAHL, Social Work Abstracts, EMBASE, and Sociology Collection databases were searched for peer-reviewed, English-language items. The vast majority of first authors were based in the UK, the US, Australia, and Canada, though UK-based authors produced over a third of included items. Forty-two journals had multiple included items. Four main, interconnected themes were identified and discussed: external rationales for change (e.g. adopting evidence-based practices, structural shifts, community demands); type and level of change (e.g. frontline interventions, restructuring management, improving internal and external relations); implementing changes (targeted interventions, broader implementation models, and successful "tactics"); and internal characteristics that both promote and inhibit change (leadership, readiness, communication, learning orientation, skills). Growing scholarship warrants frequent review and summarization for diverse actors.